Zukunftspessimismus in der Frühen Neuzeit? Überlegungen zu frühneuzeitlichen Zukunftsvorstellungen am Beispiel des Vanitas-Motives zur Zeit des Barock - Lisa-Marie Gabriel (Historia.scribere, 2017)
Future pessimism in the Early Modern era? Reflections on Early Modern future imaginations exemplified by the baroque Vanitas motif. The following bachelor thesis is about the future imaginations of the Early Modern time. The paper follows the question, if there was a factual ‚future pessimism‘ in the baroque era, trying to exemplify this by the booming Vanitas motif. Therefore, the thesis will examine the history and meaning of the motif compared to the trends of the tumultous 17th century. As will be shown, the Vanitas motif was also an art form as well as a manifestation of a transience-consciousness that manifested itself not least in the form of Vanitas still life and baroque poetry.